Room and High Temperature Tribological Behaviour of W-DLC Coatings Produced by DCMS and Hybrid DCMS-HiPIMS Configuration - Evaristo, Manuel (2020)
Carbon-based coatings are used in many applications, particularly in sliding contacts to reduce friction and wear. To improve the tribological properties, these coatings are usually alloyed with metals;Wis one of the most used since it helps improve the tribological performance at high temperatures. In this work, we compared the tribological performance of Diamond-Like Carbon alloyed with tungsten (DLC-W) films deposited by direct current magnetron sputtering (DCMS) with films deposited in a hybrid configuration DCMS + high power impulse magnetron sputtering (HiPIMS). The DLC-W coatings were produced with approximately the sameWcontent. One hydrogenated film was deposited with the hybrid configuration for comparison purposes. Microstructure, structure, mechanical properties, and tribological behaviour were used to compare the coatings. All the films displayed a low-order structure of tungsten carbide embedded in an amorphous carbon matrix. The use of the hybrid HiPIMS/DCMS results in coatings with more compact morphologies due to the high ionization fraction of the species produced on theWtarget (W and Ar ionized species), which primarily will oppose the shadowing e ect as the ions will reach the substrate at angles close to 90 . HiPIMS non-hydrogenated film is the more tribological, performing either at room or high temperature (150 C) due to the much more compact morphology, which avoids the detachment of hard W-C particles, which are responsible for more e ciently scratching the film surface. Experiments revealed that wear behaviour in all the films is governed by the contact of the tribolayer formed on the counterpart composed of W–C, C and W–O against the surface of the film.